Financial Analysis of Indian Commercial Banks: A Comparison of Various Groups - Aggarwal, Monika (Gyan Management Journal, 2010)
This paper contributes to the banking performance literature by comparing different bank groups on performance (efficiency, productivity and profitability) by using various ratios in five different owne groups in India. It focuses on the achievement and performance of State Bank group, nationalized banks, private sector banks, new private sector and foreign banks. The time period for the performance analy 1991-2007-08. The time period is fairly long, so that all the reform measures taken till date can be taken i consideration. It employs the ANOVA post hoc method for comparing different bank groups. Globaliza deregulation and World Trade Organization has lead to financial integration of markets, necessitated banking sector, which is the pillar of every economy to be financially sound and to be able to compete. It therefore, an appropriate time to assess the efficacy of various reforms and measures undertaken in the ligh. WTO in an objective quantitative manner. In general the various measures have greatly improved performance of various bank groups. But new private sector banks and foreign banks have outperformec most of the parameters. This paper is important for policy makers also, as Indian banking sector has to opened for foreign competition.fully in the future.
Keywords: Indian Banking; Profitability; Productivity; Net Interest Margin; Business per employee; ANOVA